Development of a Mosque-Center Model of Prevention of Illegal Substance Use: A Case Study of Muslim Village in Pattani Province - เจะอาแซ, รอฮานิ; โต๊ะพา, ฮัสณาฐ์; เจะแว, คอลีเยาะ; เจะโซ๊ะ, เจ๊ะยารีเย๊าะ; หนูเพชร, ฉมาพร; แวเตะ, สุไฮดาร์ (Princess of Naradhiwas University Journal, 2018)
This action research was to develop a Mosque-Center Model of Prevention of Illegal Substance Use (MCM-PISU) in a Muslim village in Pattani province, Thailand. A Muslim village in Pattani was purposively selected to participate in the study. The developmental processes of the MCM-PISU were 1) data collection of general information of the village and participants 2) Development of the MCM-PISU 3) Implementation of the MCM-PISU and 4) Evaluation of the impacts and changing of the village after implementation the MCM-PISU. Descriptive statistics such as frequency and percentage were used for describing for general information of the village and participants. Qualitative data was analysed using content analysis method. The study found that the MCM-PISU composed of 4 domains 1) development of transformative learning for members of the village from the phototype villages 2) creating of preventive environment 3) promoting of the awareness on being a good Muslim and awareness on the hazard of substances and 4) promoting of the access for medical treatment and rehabilitation. The MCM-PISU has benefit on the changing of attitude toward substance users among members of village and preventive behaviors of substance use among non-substance users and low level of substance abuse, however the changing of preventive behaviors of substance use was not observed among moderate to severe substance abuse users.